Enhancing laser speckle reduction by decreasing the pitch of a chiral nematic liquid crystal diffuser - Hansford, D; Morris, SM; Jin, Y; Elston, S (Springer Nature, 2021)
The artefact known as speckle can plague numerous imaging applications where the narrow linewidth of laser light is required, which includes laser projection and medical imaging. Here, we report on the use of thin-film chiral nematic liquid crystal (LC) devices that can be used to mitigate the influence of speckle when subjected to an applied electric field. Results are presented which show that the speckle contrast (a quantitative measure of the presence of speckle) can be significantly reduced by decreasing the pitch of the chiral nematic LC from 2700 nm to 244 nm. Further reduction in the speckle contrast can be observed by operating the diffuser technology at a temperature close to the chiral nematic to isotropic transition. At such temperatures, we observe a simultaneous improvement in the transmission of light through the device and a decrease in the electric field amplitude required for the minimum speckle contrast value. We conclude by presenting a laser projected image of the 1951 USAF target with and without the LC device to demonstrate the visual improvement as a result of the speckle reduction.